Implementation of Child Marriage Prevention Governance Based on Reproductive Health Rights Counseling for Sustainable Regeneration - Anies Marsudiati Purbadiri; Naimah Naimah; Irma Sahvitri Lawado; Siti Umiyatun Azizah; Titik Sri Astutik (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
One of the Sustainable Development Goals (SDGs) is to ensure justice and the implementation of governance that is able to maintain an increase in the quality of life from generation to generation, including the Millennial Generation who were born on average in 1997-2012 or aged 8-23 years, including by preventing child marriage. This is because child marriage does not meet the requirements for the validity of marriage as stated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, does not comply with the expectations of Law Number 36 of 2009 concerning Health and is not in line with the Sustainable Development Goals Point 5.3, including not supporting the implementation of Lumajang Regent Regulation Number 23 of 2020 concerning the Prevention of Child Marriage, so that intensive legal counseling is needed. The goal is that child marriage will no longer be a prominent issue and hinder the pace of development, along with growing public awareness of the risks that accompany it, especially regarding women's reproductive health. The methods used are a legal approach and a case approach by presenting primary and secondary data. The expected result is that with comprehensive governance, improvements in the quality of life of the next generation can be achieved in connection with the existence of synergistic cross-generational concern in understanding the importance of upholding reproductive rights amidst the phenomenon of child marriage..Thus, understanding reproductive rights as a means of reducing the number of child marriages can be a positive contribution to improving the quality of life of future generations.